2001
DOI: 10.1097/00000539-200101000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine Wound Instillation via an Electronic Patient-Controlled Analgesia Device and a Double-Catheter System Does Not Decrease Postoperative Pain or Opioid Requirements After Major Abdominal Surgery

Abstract: After major abdominal surgery performed through a 20-cm incision, repeated 0.25% bupivacaine wound instillation via an electronic patient-controlled analgesia device and a double-catheter system does not decrease postoperative pain or opioid requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 7 publications
1
54
1
4
Order By: Relevance
“…Several studies have reported on use of pre-emptive local anaesthetics (local anaesthetic given during the operation to prevent or reduce pain afterwards) to relieve postoperative pain, with results ranging from being beneficial 5,6 to conferring no benefit. 7,8 The local anaesthetic may be administered by pre-or postincisional abdominal nerve block (local anaesthetic injected to block the nerves before cutting the skin at the beginning of the operation, or after closing the skin at the end 9 ) or pre-or post-incisional abdominal wound infiltration. 5,10 It may also be administered by continuous wound irrigation.…”
mentioning
confidence: 99%
“…Several studies have reported on use of pre-emptive local anaesthetics (local anaesthetic given during the operation to prevent or reduce pain afterwards) to relieve postoperative pain, with results ranging from being beneficial 5,6 to conferring no benefit. 7,8 The local anaesthetic may be administered by pre-or postincisional abdominal nerve block (local anaesthetic injected to block the nerves before cutting the skin at the beginning of the operation, or after closing the skin at the end 9 ) or pre-or post-incisional abdominal wound infiltration. 5,10 It may also be administered by continuous wound irrigation.…”
mentioning
confidence: 99%
“…After screening, 5 randomised controlled trials were identified [22][23][24][25][26] . The five trials included 542 laparotomy wounds, of which 259 were randomised to infusion of local anaesthetic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Opioid consumption: Four of the five trials reported total opioid consumption with or without local anaesthetic wound infusions [22][23][24][25] ( Figure 1A). Local anaesthetic wound infusion was associated with a significant decrease in total opioid consumption (weighted mean difference: -40.13; 95% CI: -76.74 to -3.53; P = 0.03).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…3,4 The local anaesthetic may be administered by pre or postincisional abdominal nerve block (local anaesthetic injected to block the nerves before cutting the skin at the beginning of the operation, or after closing the skin at the end) 5 or pre-or postincisional abdominal wound infiltration. 1,6 Local anaesthetics eventually get absorbed systemically and secreted in breast milk, but their effects on breastfed babies have not yet been documented.…”
mentioning
confidence: 99%